2021
DOI: 10.31219/osf.io/ufpgx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic and Social Impacts of Social Entrepreneurship Implementation Service to Community

Abstract: The government's policy to prevent the spread of COVID-19 has limited physical interaction between communities, creating problems for various everyday economic activities. One of which is the existence of a grant given by the Ministry of Research and Technology / National Innovation Research Agency of the Republic of Indonesia for the implementation of community service by guiding the development of micro?businesses in society. This type of research is a descriptive method with a qualitative approach. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…The work environment exists in the workers' environment and can influence them in carrying out tasks such as temperature, humidity, ventilation, lighting, noise, cleanliness of the workplace, and whether or not work equipment is adequate (Ahdan et al, 2019;Mustafa et al, 2020;Tamsah et al, 2020). The work environment can be interpreted as the entire toolbox, the surrounding environment in which a person works, the method of work, and the influence of his work both as an individual and as a group (Prakoso et al, 2021;Sahid et al, 2020;Usman et al, 2020;Yusriadi et al, 2020;Zacharias et al, 2021). The work environment is where employees do their daily work (Setiawan et al, 2021;Tamsah et al, 2021).…”
Section: Results and Discussion Employee Work Environmentmentioning
confidence: 99%
“…The work environment exists in the workers' environment and can influence them in carrying out tasks such as temperature, humidity, ventilation, lighting, noise, cleanliness of the workplace, and whether or not work equipment is adequate (Ahdan et al, 2019;Mustafa et al, 2020;Tamsah et al, 2020). The work environment can be interpreted as the entire toolbox, the surrounding environment in which a person works, the method of work, and the influence of his work both as an individual and as a group (Prakoso et al, 2021;Sahid et al, 2020;Usman et al, 2020;Yusriadi et al, 2020;Zacharias et al, 2021). The work environment is where employees do their daily work (Setiawan et al, 2021;Tamsah et al, 2021).…”
Section: Results and Discussion Employee Work Environmentmentioning
confidence: 99%
“…Most of the malpractice cases that occurred in Indonesia, as an alternative for resolving issues in the medical field, ended only with criminal mediation. In addition, only those who end up with compensation for the victim's family from a crime in the medical area, even though there are still many families of the victim who still feel it is inappropriate to pay compensation only because the perpetrators of medical crimes do not get criminal sanctions, do not provide a deterrent effect on the perpetrators but the victims must sue (Ansar et al, 2019;Ilyas et al, 2021;la Kamalussin et al, 2021;Mislia et al, 2021;Nellyanti et al, 2021;Prakoso et al, 2021;Sawitri et al, 2019;Umar, Amrin, et al, 2019;Usman et al, 2020;Yusriadi et al, 2020;Zamad et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When calculated with a population of Indonesia's population at around 273 million people, the number of national business people barely held out at 9.55 million people, and it can be concluded that it is still very low (Irawati & Wantara, n.d.;Rohaeni et al, 2021). Looking at these facts, entrepreneurs are going to have an impact on economic advancement and the enhancement of Indonesia's economic position (Yusriadi et al, 2020). To want to be a businessman, it is necessary to identify and understand possibilities, assemble necessary resources, and then act to capitalize on those opportunities (Ahmad & Hoffmann, 2011;Cooney, 2012;Kerr et al, 2018).…”
Section: Figure 4 Open Unemployment Rate By Education Levelmentioning
confidence: 99%